Case reportIs only severe vascular tortuosity a contraindication for the transfemoral approach of transcatheter aortic valve implantation? - Aykan, Ahmet ÇagrI; Gökdeniz, Tayyar; Tarik Agaç, Mustafa; Çelik, Șükrü (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Transcatheter aortic valve implantation is an alternative therapy for surgery in patients with aortic stenosis having high risk for surgery. Transcatheter aortic valve implantation may be performed through transfemoral, transaortic and transapical approaches. General anesthesia is generally required for transapical and transaortic approaches while epidural anesthesia is enough for the transfemoral approach. Although transfemoral access is suitable for most cases, patients having severe vascular tortuosity are candidates for the transapical approach. However, the approach for patients having vascular tortuosity along with poor respiratory capacity contraindicated for general anesthesia is controversial. Vascular complications that significantly increase patient morbidity and mortality are common in transfemoral transcatheter aortic valve implantation and generally associated with severe ilio-femoral tortuosities, severe calcification, porcelain aorta, and significant atheroma of the femoral and iliac vessels. But the effect of tortuosity alone was not evaluated well and complications were generally associated with vascular calcification. Stiff wires were commonly used in endovascular procedures. The vascular tortuosity can be straightened with stiff wires but the accordion effect, pseudo obstruction and vascular injury may also be observed. Herein we present a case of severe aortic stenosis successfully treated with transfemoral aortic valve implantation despite severe femoral, iliac and aortic tortuosity having severe chronic obstructive pulmonary disease.